COT phosphorylates prolyl‐isomerase Pin1 to promote tumorigenesis in breast cancer. Issue 6 (22nd November 2013) - Kim, Garam; Khanal, Prem; Kim, Jin Young; Yun, Hyo‐Jeong; Lim, Sung‐Chul; Shim, Jung‐Hyun; Choi, Hong Seok
<x xml:space="preserve">Abstract</x> Pin1, a conserved eukaryotic Peptidyl‐prolyl cis/trans isomerase, has profound effects on numerous key‐signaling molecules, and its deregulation contributes to disease, particularly cancer. Although Pin1‐mediated prolyl isomerization is an essential and novel regulatory mechanism for protein phosphorylation, little is known about the upstream signaling pathway(s) that regulates Pin1 activity. Here, we identify MAP3K‐related serine–threonine kinase (the gene encoding COT/Tpl2) as a kinase responsible for phosphorylation of Pin1 Ser16. COT interacts with and phosphorylates Pin1 on Ser16. Consequently, Pin1 Ser16 phosphorylation by COT increases cyclin D1 abundance and enhances tumorigenecity of MCF7 cells. In contrast, depletion of COT in MCF7 cells leads to downregulation of Pin1 Ser16 phosphorylation, which subsequently decrease cyclin D1 levels, inhibiting tumorigenecity of MCF7 cells. In a xenograft model, treatment of TKI, a COT inhibitor, and Juglone, a Pin1 inhibitor, abrogates tumor growth. In human breast cancer patients, immunohistochemical staining shows that Pin1 pSer16 levels are positively correlated with COT levels, providing strong evidence for an essential role of the COT/Pin1 axis in conveying oncogenic signals to promote aggressiveness in human breast cancer. © 2013 Wiley Periodicals, Inc.